MULTIFACTORIAL DETERMINANTS OF PRETERM BIRTH: A REVIEW OF CURRENT RISK FACTORS AND PREVENTIVE STRATEGIES - Karolina Alicja Krystyniak; Katarzyna Anna Kowalska; Jakub Tomasz Latos; Franciszek Szweda; Tomasz Poczwardowski; Adrianna Kaczmarek; Marcin Chwalczuk; Olivia Grygorcewicz; Marta Koneczna; Kinga Augustyniak; Natalia Smuniewska; Zofia Grodzka (International Journal of Innovative Technologies in Social Science, 2026)
Preterm birth is one of the most serious challenges in modern perinatology, being a significant cause of morbidity and mortality in newborns and long-term health complications. PTB affects approximately 15,000,000 children worldwide each year and accounts for approximately 11% of births globally. It is responsible for a significant proportion of perinatal morbidity and mortality, as well as long-term neurological, metabolic, and developmental complications in children. The aim of this review was to summarize the current knowledge on the risk factors for preterm birth and to organize the most important ones. Preterm birth is a phenomenon with a complex etiology, and its risk results from the interaction of biological, obstetric, and environmental factors. The identification and modification of selected factors, especially those related to the mother's lifestyle and nutritional status, is a key element of prevention and prenatal care. Based on the available data, the clinical importance of early identification of risk factors and the implementation of preventive strategies and monitoring of high-risk pregnancies has been emphasized. A better understanding of the mechanisms leading to preterm birth may contribute to reducing the incidence of this complication and improving the prognosis for newborns.